A new negative air ion smoke suppression purifier for purifying fire smoke in road tunnel based on corona discharge - Shouzhong Feng; Deyuan Kan; Zhiguo Yan; Weixing Mao; Long Zhou (Results in Engineering)
The enclosed environment of a road tunnel restricts the dispersion of fire smoke, leading to its rapid accumulation, which significantly hampers firefighting efforts and personnel evacuation. Therefore, exploring more effective methods for smoke control is essential. This study evaluates the feasibility of negative air ion purifiers for suppressing tunnel fire smoke through full-scale tests. The purification performance of the purifiers at various installation heights was assessed by analyzing the concentration of negative air ions, the variation in fine particulate matter levels, and smoke distribution inside the tunnel. Additionally, an eye tracker was employed to record the pupil change data of the testers before and after the negative ion smoke suppression purifier was used to measure changes in pupil diameter before and after activating the purifier system to evaluate its impact on alleviating the physiological and psychological stress of individuals in the fire environment. The results indicate that installing the purifiers at 2.5 m and 3.5 m on the sidewall achieves optimal purification, with sufficient negative air ions concentrations and reduced fine particulate matter levels. From a visual perspective, after the purifier system is activated, smoke stratification is enhanced, and its downward spread is limited, resulting in improved smoke control within the tunnel.